AGRICULTURAL LAND IN THE CONTEXT OF THE THEORY OF PUBLIC GOODS – CRITICAL ANALYSIS - Maśniak, Jacek (Acta Scientiarum Polonorum. Oeconomia, 2019)
The main purpose of this article is to present a critical point of view towards the application of the public goods concept to land and agriculture. The basic legal regulations forming the agricultural system in Poland and the assessment of the legitimacy of state interventions on the land market in the light of the theory of the Austrian school of economics are discussed. According to the criteria used in the theory of public goods, agricultural land is a typical private good. On the other hand, the issue of goods integrally connected with land such as agricultural landscape and quality of the natural environment is debatable. The following arguments are against the state intervention: the lack of the possibility to objectively identify social needs, the political and redistributive nature of state intervention, the existence of market mechanisms for financing public goods.